Peran Pendidikan Kewarganegaraan dalam Menanamkan Nilai Moralitas pada Siswa Sekolah Dasar: The Role of Civic Education in Instilling Moral Values ??in Elementary School Students - Damanik, Maulidya Hasanah; Saragi, Daulat; Ndona, Yakobus (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Instilling moral values in elementary school students is an important foundation in the formation of the character of the younger generation. Civic Education, as one of the compulsory subjects in elementary school, has great potential in instilling moral and ethical values in students. However, the effectiveness of Civic Education in achieving this goal still needs to be studied further. This research method is a conceptual qualitative research using the Library Research method, which is carried out by collecting Secondary Data in the form of data from scientific articles or scientific papers, research journals, and reports related to the chosen topic. The results of the study indicate that Civic Education has a significant role in instilling moral values in elementary school students. The effectiveness of instilling these values is influenced by several factors, including: (1) interactive and experience-based learning methods, (2) teacher role models in implementing moral values, (3) integration of moral values in daily activities at school, and (4) collaboration between schools and parents in strengthening the values taught. Civic Education has proven to be effective in instilling moral values in elementary school students. However, this success depends on a holistic approach involving various parties and the right learning methods. This study recommends the need to develop a more contextual civics curriculum and improve teacher competence in integrating moral values in learning.